Foreign objects debris (FOD) identification: a cost effective investigation of FOD with less false alarm rate - Khan, Talha Ahmed; Alam, Muhammad; Kadir, Kushairy; Shahid, Zeeshan; Mohd Su'ud, Mazliham; Khan, Sheroz; Miqdad, Mohammad (Institute of Electrical and Electronics Engineers Inc., 2018)
Foreign Objects Debris (FOD) at Airports can be considered as a main cause of accidents that includes aircrafts damage, infrastructure and human lives loss. Therefore, Foreign Objects Debris (FOD) is the topmost intimidation for the security of aviation, airports, aircrafts and passengers. It is very complex to identify the Foreign Objects Debris (FOD) due to its diversification is size and volume. For the security of aviation and passengers, robust Foreign Objects Debris (FOD) identification system is needed. Various research approaches have been carried out for the accurate and precise investigation of Foreign Objects Debris (FOD). In this research paper we have proposed a cost effective Foreign Objects Debris (FOD) detection solution with less false alarm rate compared to the other existing trends. To accomplish the task, we designed a prototype comprised of curtain sensor as primary transducer and an ultrasonic proximity sensor as a secondary transducer along with a camera with image processing algorithm. Experimental results proved that rapid identification of Foreign Objects Debris (FOD) by our proposed research worked better than the other available techniques economically.